Correction to: Efficacy of intravenous plus intrathecal/intracerebral ventricle injection of polymyxin B for post-neurosurgical intracranial infections due to MDR/XDR Acinectobacter baumannii: a retrospective cohort study - Sijun Pan; Xiaofang Huang; Yesong Wang; Li Li; Changyun Zhao; Zhongxiang Yao; Wei Cui; Gensheng Zhang (Antimicrobial Resistance and Infection Control, 2019)
The original article [1] contains an error in the Safety analysis sub-section of the results regarding the reported mean creatinine level.